2020
DOI: 10.1038/s41467-020-16980-5
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of evolving nanostructures in ultrathin films with X-ray waveguide fluorescence holography

Abstract: Controlled synthesis of nanostructure ultrathin films is critical for applications in nanoelectronics, photonics, and energy generation and storage. The paucity of structural probes that are sensitive to nanometer-thick films and also capable of in-operando conditions with high spatiotemporal resolutions limits the understanding of morphology and dynamics in ultrathin films. Similar to X-ray fluorescence holography for crystals, where holograms are formed through the interference between the reference and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…With respect to nanomaterial development and quality management applications in the semiconductor industry, it is also valuable to take advantage of the optical equivalence With respect to nanomaterial development and quality management applications in the semiconductor industry, it is also valuable to take advantage of the optical equivalence of grazing incidence and grazing emission XRF (GI-and GEXRF) principles. The GEXRF approaches have been successfully explored for more than two decades at various large-scale facilities and in academic laboratories [75][76][77][78][79][80][81], in particular regarding the characterization of nanolayered systems. To complement angular GIXRF studies [22,72] and related reconstruction works on nanostructures [73], GEXRF also allows for the scanning-free detection of the angular distribution of fluorescence radiation emitted by a nanostructure using position-sensitive detectors such as CCDs or CMOS devices [82].…”
Section: Hybrid Metrology-determination Of Dimensional and Analytical...mentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to nanomaterial development and quality management applications in the semiconductor industry, it is also valuable to take advantage of the optical equivalence With respect to nanomaterial development and quality management applications in the semiconductor industry, it is also valuable to take advantage of the optical equivalence of grazing incidence and grazing emission XRF (GI-and GEXRF) principles. The GEXRF approaches have been successfully explored for more than two decades at various large-scale facilities and in academic laboratories [75][76][77][78][79][80][81], in particular regarding the characterization of nanolayered systems. To complement angular GIXRF studies [22,72] and related reconstruction works on nanostructures [73], GEXRF also allows for the scanning-free detection of the angular distribution of fluorescence radiation emitted by a nanostructure using position-sensitive detectors such as CCDs or CMOS devices [82].…”
Section: Hybrid Metrology-determination Of Dimensional and Analytical...mentioning
confidence: 99%
“…of grazing incidence and grazing emission XRF (GI-and GEXRF) principles. The GEXRF approaches have been successfully explored for more than two decades at various largescale facilities and in academic laboratories [75][76][77][78][79][80][81], in particular regarding the characterization of nanolayered systems. To complement angular GIXRF studies [22,72] and related reconstruction works on nanostructures [73], GEXRF also allows for the scanning-free detection of the angular distribution of fluorescence radiation emitted by a nanostructure using position-sensitive detectors such as CCDs or CMOS devices [82].…”
Section: Operando Metrology-time-resolved Determination Of the Analyt...mentioning
confidence: 99%
“…XWFH is a recently developed high-resolution probe for atom or nanoparticle depth profiling in thin films. While the principle and experimental considerations are described in detail elsewhere (Jiang et al, 2020), they are briefly illustrated here via an example [Fig. 5(a)].…”
Section: X-ray Waveguide Fluorescence Holography For Gold-layer Depth...mentioning
confidence: 99%
“…Model assessment and selection methods help determine the number of splines N S . In this example, we evaluated models with different N S and found that approximately 30 splines (thus 30 unknown spline coefficients) are required to give a sensible result (Jiang et al, 2020). Assuming no prior knowledge about this profile, we set a constant value for all the initial spline coefficients.…”
Section: X-ray Waveguide Fluorescence Holography For Gold-layer Depth...mentioning
confidence: 99%
“…In 2011, Kim et al [88] obtained the reconstructed image of nanomaterials with the resolution of 87 nm with single-shot Fourier-transform X-ray holography and X-ray laser. In 2020, Zhang et al [89] reconstructed the evolved nanostructures in ultrathin films with X-ray waveguide fluorescence holography. e analysis results showed that the controllable synthesis of nanostructure ultrathin films may become a reality.…”
Section: Industrial Fieldmentioning
confidence: 99%